Risk of suicide after discharge from inpatient psychiatric care: a systematic review. (2nd November 2021) - O'Connell, Patrick H.; Durns, Tyler; Kious, Brent M.
Abstract: Objective: The period following discharge from inpatient psychiatric care is recognised as an especially high-risk time for patient suicide. Astonishingly, there is a dearth of comprehensive studies examining risk and protective factors in this specific population. The aim of this study was to establish the protective and risk factors for suicide in the first year post-discharge (PD) from psychiatric facilities and their utility in categorising patients as high or low risk in a meaningful way to benefit clinical care and improve patient outcomes. Methods: A methodical search of three databases (PubMed, EMBASE, and PsychINFO) was used to identify reports describing risk factors for suicide after psychiatric discharge. Results: Predominantly, male sex, a history of self-harm, a history of suicide attempts, admission with suicidal ideation or suicidal behaviour, and hopelessness were identified as being associated with death by suicide after discharge. Lithium appeared to be protective against suicide in the studies reviewed. Other variables examined showed mixed results. Conclusions: The findings of this review suggest that significant suicide predictors both common and unique to those established for suicide in the general population exist and can be utilised in a clinically meaningful way, despite the difficulties inherent in studying this population. KEY POINTS: The risk of suicide after psychiatric hospitalisation is high. Factors that predict suicide after psychiatric hospitalisation overlap only partially with risk factors for suicide in general. Important risk factors for suicide in the post-discharge period include male sex, a history of self-harm, a history of suicide attempts, the presence of suicidal ideation during the admission, and hopelessness. The conclusions that can be drawn from the existing literature are limited by small study sizes, different study populations, and different follow-up periods; additional research in this domain is needed.